(untitled) (Journal of Nepal Geological Society, 2019)
Liquefaction is generally experienced in unconsolidated fine- grained sediments during the large earthquakes. In Nepal, the southern part of the country comprises Quaternary deposits called as Indo-Gangetic deposit. Sand and silts are dominant in this zone, where groundwater level is also relatively high. In eastern Nepal, several places have experienced ground fissures, sand boiling, and liquefaction during the large earthquakes in the past history. There are several factors including soil properties, groundwater level, grain size of sediments and ground acceleration that contribute to ground liquefaction. The eastern Nepal faced a devastating earthquake in 1934 (magnitude of 8.4), Udaypur earthquake in 1988 (magnitude of 6.6) and Sikkim-Nepal earthquake in 2011 (magnitude of 6.8) and there is still possibility of similar large earthquakes in future. Liquefaction was reported in many places during Nepal-Bihar earthquake that indicates possibility of liquefaction during similar earthquakes. Liquefaction potential values are calculated from sediment grain size, subsurface geology, groundwater level and standard penetration test (SPT)-N values. The epicenter, magnitude, and other parameters of Nepal-Bihar earthquake have been used to calculate the liquefaction potential. A liquefaction susceptibility map has been prepared in the study area that comprises low, medium, and high liquefaction potential zones. About 20% of the study area including Jhapa Bazar and its surrounding area seems highly susceptible to liquefaction.